2016
DOI: 10.1016/j.bbr.2016.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Binge ethanol withdrawal: Effects on post-withdrawal ethanol intake, glutamate–glutamine cycle and monoamine tissue content in P rat model

Abstract: Alcohol withdrawal syndrome (AWS) is a medical emergency situation which appears after abrupt cessation of ethanol intake. Decreased GABA-A function and increased glutamate function are known to exist in the AWS. However, the involvement of glutamate transporters in the context of AWS requires further investigation. In this study, we used a model of ethanol withdrawal involving abrupt cessation of binge ethanol administration (4 g/kg/gavage three times a day for three days) using male alcohol-preferring (P) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(58 reference statements)
3
16
0
Order By: Relevance
“…The synthesized compounds were initially screened at 10 μM final concentration against recombinant human MAO-A and MAO-B by using 1-methyl-4–(1-methylpyrrol-2-yl)-1,2,3,6-tetrahydropyridine (MMTP) as a nonselective substrate for both MAO-A and B. It is important to note that the K m values for human MAO-A and MAO-B were found to be 88 μM and 101 μM, respectively, and this is in accordance with previously reported values 26 , 27 . The formation of the dihydropyridinium species (MMDP + ) as a MAO-catalyzed oxidation product of MMTP was monitored at 420 nm.…”
Section: Resultssupporting
confidence: 90%
“…The synthesized compounds were initially screened at 10 μM final concentration against recombinant human MAO-A and MAO-B by using 1-methyl-4–(1-methylpyrrol-2-yl)-1,2,3,6-tetrahydropyridine (MMTP) as a nonselective substrate for both MAO-A and B. It is important to note that the K m values for human MAO-A and MAO-B were found to be 88 μM and 101 μM, respectively, and this is in accordance with previously reported values 26 , 27 . The formation of the dihydropyridinium species (MMDP + ) as a MAO-catalyzed oxidation product of MMTP was monitored at 420 nm.…”
Section: Resultssupporting
confidence: 90%
“…(Reissner and Kalivas, 2010). It is noteworthy, that we did not find any significant changes in xCT expression in EtOH compared with water group which is consistent with our previous findings that xCT was not downregulated in binge EtOH drinking (Das et al, 2016). There is possibility that ETOH or MA may induce dysfunction of xCT without affecting its expression.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, however, rats were gavaged with EtOH (6 g/kg) for 7 days, which represent the repeated binge dosing paradigm of EtOH (Faingold, 2008). In addition, it has been shown that rats administered EtOH using a binge gavage protocol (4 g/kg, 3 to 4 times a day) reduced GLT-1 expression in the nucleus accumbens, medial prefrontal cortex and striatum (Das et al, 2016; Abulseoud et al, 2014). Interestingly, MA and EtOH exposure has synergistic effect in the downregulation of GLT-1 expression as compared to either drug administered alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…every 2 h × 4) exposure was chosen based on previous studies that showed neurotoxicity and elevation of extracellular glutamate concentration in rat brains (Bowyer et al, 1994 ; Hirata et al, 1995 ; Yamamoto and Zhu, 1998 ; Mark et al, 2004 , 2007 ). The rationale for testing the ethanol binge gavage paradigm was based on recent studies from our laboratory and others (Faingold, 2008 ; Abulseoud et al, 2014 ; Das et al, 2016 ). Control and treated rats were then quickly euthanized by CO 2 inhalation and rapidly decapitated.…”
Section: Methodsmentioning
confidence: 99%